From Rumour to Métis Urban Legend: François Guilmette and the Execution of Thomas Scott - Nault, Derrick (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2025)
This article discusses the urban legend of François Guilmette, an alleged participant in the 1870 execution of Thomas Scott during the Red River Resistance. Applying Linda Dégh’s theory of the “legend process,” the study traces how the story of Guilmette evolved from a vague rumour to an accepted fact after first appearing in 1874 legal proceedings. From the 1880s onward, historians and community narratives wove Guilmette into accounts of the Resistance, adding further details about his death and even linking him to an iconic photograph featuring Louis Riel. While Métis and their stories are often associated with rural, “traditional” settings, this analysis reveals how the uncertainty associated with the transfer of Rupert’s Land to Canada provided ideal conditions for the emergence of a distinctly Métis urban legend that persists in collective memory to this day.